I just want to matter: Examining the role of anti-mattering in online suicide support communities using natural language processing. (February 2023) - Deas, Nicholas; Kowalski, Robin; Finnell, Sophie; Radovic, Emily; Carroll, Hailey; Robbins, Chelsea; Cook, Andrew; Hurley, Kenzie; Cote, Natalie; Evans, Kelly; Lorenzo, Isabella; Kiser, Kelly; et al.
Abstract: Annually, tens of thousands of lives are affected by suicide, including those who die by suicide, attempt non-fatal suicidal behaviors, and suffer from suicidal thoughts and ideation as well as friends and family affected by the loss of loved ones. Although a number of predictors of suicidal thoughts and behaviors have been examined in the literature, the current study investigated the presence of anti-mattering and suicidal ideation in online peer support communities through the r/SuicideWatch subreddit community. A historical archive of posts made in the subreddit was collected using the Python Reddit API Wrapper (PRAW), resulting in a final anonymized corpus of 500, 548 posts. A sample of 1, 700 posts were hand-labeled for the presence of anti-mattering and other constructs in order to train and evaluate a classification model for automated labeling. Using the resulting model and keyword dictionaries, the entire corpus was labeled, informing a nomological network of anti-mattering in online peer-support communities. Highlights: People who feel that they don't matter seek out help in online communities. Anti-mattering coded in nearly 70% of posts on r/SuicideWatch. Anti-mattering correlates with loneliness, stress from others, shame, absolute talk, mental health, loss, and hopelessness. Suicide prevention/intervention programs should work to increase feelings of mattering.